IBN KATHIR'S INTERPRETATION OF FEMALE DESIRE: A CRITICAL ANALYSIS OF SURAH YUSUF VERSE 31 - Manggala, Kayan; Istiadah, Istiadah; Hamidah, Tutik; Barizi, Ahmad; Arifin, Syamsul (EGALITA, 2025)
Abstract This study critically examines the representation of female desire in Surah Yusuf, verse 31, through the lens of Ibn Kathir’s classical tafsir. Despite growing scholarly attention to gender and sexuality in Islamic texts, focused analyses of female desire within Qur’anic exegesis remain limited. Addressing this gap, the present research offers a pioneering contribution by employing a qualitative descriptive method to analyze both linguistic and interpretative dimensions of the verse. The study pursues three main objectives: (1) to investigate the linguistic nuances and variations across major English translations of the verse; (2) to explore Ibn Kathir’s interpretive framing of the narrative involving the women of Egypt; and (3) to analyze how the concept of female desire is constructed within his tafsir. The findings reveal significant disparities in how translations convey the intensity and consequences of the women’s attraction to Prophet Yusuf. Ibn Kathir’s exegesis characterizes their behavior as influenced by both individual and collective longing, catalyzed by Yusuf’s extraordinary beauty. Notably, the tafsir identifies elements such as physical attraction, emotional overwhelm, and even metaphorical “drunkenness” as markers of female desire. This study contributes to the broader discourse on gender in Islamic thought by highlighting how classical interpretations engaged with complex emotional and psychological dimensions of female figures in the Qur’an. By revisiting these exegetical traditions, the research fosters a more nuanced and historically grounded understanding of female desire, offering critical insights for contemporary debates on gender, sexuality, and the interpretation of sacred texts. Keywords: Female Desire; Surah Yusuf; Ibn Kathir’s Interpretation.Abstrak Penelitian ini secara kritis mengkaji representasi hasrat perempuan dalam Surah Yusuf ayat 31 melalui tafsir klasik Ibn Kathir. Meskipun kajian akademik mengenai gender dan seksualitas dalam teks-teks Islam semakin berkembang, analisis yang secara khusus membahas hasrat perempuan dalam konteks tafsir Al-Qur’an masih sangat terbatas. Untuk menjembatani kekosongan ini, penelitian ini menawarkan kontribusi awal dengan menggunakan metode deskriptif kualitatif guna menganalisis dimensi linguistik dan interpretatif dari ayat tersebut. Penelitian ini memiliki tiga tujuan utama: (1) menyelidiki nuansa kebahasaan dan variasi dalam sejumlah terjemahan bahasa Inggris utama terhadap ayat tersebut; (2) mengeksplorasi cara Ibn Kathir membingkai narasi tentang para perempuan Mesir; dan (3) menganalisis bagaimana konsep hasrat perempuan dikonstruksikan dalam tafsirnya. Hasil penelitian menunjukkan adanya perbedaan yang signifikan dalam cara terjemahan menggambarkan intensitas dan konsekuensi dari ketertarikan para perempuan terhadap Nabi Yusuf. Tafsir Ibn Kathir menggambarkan perilaku mereka sebagai hasil dari hasrat individu maupun kolektif, yang dipicu oleh pesona luar biasa Yusuf. Menariknya, tafsir ini mengidentifikasi unsur daya tarik fisik, gejolak emosi, hingga “mabuk” secara metaforis sebagai penanda dari hasrat perempuan. Studi ini memberikan kontribusi penting bagi diskursus gender dalam pemikiran Islam dengan menyoroti bagaimana tafsir klasik merespons dimensi emosional dan psikologis tokoh-tokoh perempuan dalam Al-Qur’an. Dengan meninjau kembali tradisi tafsir tersebut, penelitian ini menghadirkan pemahaman yang lebih mendalam dan historis tentang hasrat perempuan, sekaligus menawarkan wawasan kritis bagi perdebatan kontemporer mengenai gender, seksualitas, dan penafsiran teks suci. Kata Kunci: Syahwat Wanita; Surat Yusuf; Tafsir Ibnu Katsir.